Fully Automated HTML and JavaScript Rewriting for Constructing a Self‐healing Web Proxy. (14th February 2020) - Durieux, Thomas; Hamadi, Youssef; Monperrus, Martin
Summary: Over the last few years, the complexity of web applications has increased to provide more dynamic web applications to users. The drawback of this complexity is the growing number of errors in the front‐end applications. In this paper, we present an approach to provide self‐healing for the web. We implemented this approach in two different tools: (i) BikiniProxy, an HTTP repair proxy, and (ii) BugBlock, a browser extension. They use five self‐healing strategies to rewrite the buggy HTML and JavaScript code to handle errors in web pages. We evaluate BikiniProxy and BugBlock with a new benchmark of 555 reproducible JavaScript errors of which 31.76% can be automatically self‐healed by BikiniProxy and 15.67% by BugBlock. Abstract : In this paper, we propose an HTTP‐proxy and a browser extension bring self‐healing abilities to existing web applications. They use five self‐healing strategies to rewrite the buggy HTML and Javascript code to handle errors in web pages. We evaluate the technique on reproducible Javascript errors, of which 31.76% can be automatically self‐healed by the HTTP‐proxy and 15.67% by the browser extension.